Analysis on Spatio-Temporal Variability of Fractional Vegetation Cover and Influencing Factors from 2000 to 2020 in Southwestern China - Yuting LIU; Lei WANG; Xiehui LI; Lei GUO (Gaoyuan qixiang)
The southwestern China is a vital ecological safeguard and is characterized by ecological fragility and climate sensitivity.Based on the MOD13A3 NDVI dataset， this study used a pixel dichotomy model to calculate the average Fractional Vegetation Cover （FVC） from 2000 to 2020 annually， during growing seasons， and in each of the four seasons for the whole southwestern China and its provinces， a spatio-temporal variation analysis was then performed on FVC across different time scales.The study also discussed the primary factors influencing FVC changes over the past 21 years， using ERA5 temperature data， GPCP satellite precipitation data， and DEM data.Finally， the Hurst Index was used to predict future FVC trends.（1） The results indicate that from 2000 to 2020， the overall FVC in the eastern part of the southwestern China showed an increasing trend， particularly in Chongqing and Guizhou， while Tibet showed a general decline.（2） Spatially， the FVC generally showed a "higher in the east and lower in the west" trend， with areas where FVC increased accounting for 43.9% of the total area， and areas of decrease accounting for 53.5%.（3） Precipitation promotes FVC， while temperature has varied effects in different regions.（4） Human activity significantly impacts FVC， with promotion， suppression， and no effect zones accounting for 40.4%， 47.6%， and 12.0% of the grid percentage， respectively.（5） Elevation and FVC over different time scales are significantly correlated but both exhibit a pronounced declining trend.FVC increases significantly with slope， but decreases when the slope is greater than 25°.The effect of aspect on FVC in the southwestern China is less significant than that of slope， elevation， and climatic factors.（6） In the future， the FVC in Tibet and the eastern parts of Sichuan， Yunnan， and Guizhou in the southwestern China will increase， while most areas of western Sichuan and the Hengduan Mountains will exhibit a decreasing trend.The results can provide data support and scientific guidance for the formulation of ecological protection plans in the southwestern China.